Transmissible gastroenteritis virus N protein causes endoplasmic reticulum stress, up-regulates interleukin-8 expression and its subcellular localization in the porcine intestinal epithelial cell. (August 2018) - Zhang, Qi; Xu, Ying; Chang, Rong; Tong, Dewen; Xu, Xingang
Abstract: This essay focuses on transmissible gastroenteritis virus (TGEV), which is an enteropathogenic virus related to contagious and acute diseases in suckling piglets. Previous literature suggests that the TGEV nucleocapsid protein (N) plays a significant role in viral transcriptional process, however, there is a need to examine other functions of TGEV N protein in the porcine intestinal epithelial cell (IEC) which is the target cell of TGEV. In the present study, we investigated the degradation, subcellular localisation, and function of TGEV N protein by examining its effects on cycle progression, endoplasmic reticulum (ER) stress, interleukin-8 (IL-8) expression, and cell survival. The results showed that TGEV N protein localised in the cytoplasm, inhibited IEC growth, prolonged the S-phase cell cycle by down-regulating cell cycle protein cyclin A, and was mainly degraded through the proteasome pathway. Moreover, TGEV N protein induced ER stress and activated NF-κB, which was responsible for the up-regulation of IL-8 and Bcl-2 expression. This report mainly considers the functions of TGEV N protein in IEC. To be specific, in IEC, TGEV N protein induces cell cycle prolongation at the S-phase, ER stress and up-regulates IL-8 expression. These results provide a better understanding of the functions and structural mechanisms of TGEV N protein. Highlights: This is the first report about the function of TGEV N protein in the host cell. We investigate that TGEV N protein is located in the cytoplasm. N protein prolongs the S-phase cell cycle by down-regulating cyclin A's expression. TGEV N protein could higher levels of IL-8 and Bcl-2 expression in IEC. TGEV N protein induces ER stress and activates NF-κB pathway.